Less Is More in Digital Games Too: A Comparative Analysis of Visual Elements of Physical and Digital Versions for Two Tabletop Games - Darijo Čerepinko; Robert Štefanović; Krunoslav Hajdek; Petar Miljković (Applied Sciences)
The changing habits of consuming entertainment via digital channels have been well researched in contemporary academic papers, as has the migration of different forms and formats into digital environments. Often these migrations are based on familiarity for facilitating the smooth transition into the new format, with additions specific to the digital channel (e.g., animations, sound effects, 3D perspectives, etc.) that are supposed to enhance user experience. In this paper, we present a comparative study of visual elements used in physical and digital versions of two tabletop games (Monopoly and UNO). Results from a sample of 100 players of both versions show higher overall satisfaction when engaging with the physical version of the games and significantly lower satisfaction with various visual elements in digital versions, such as overall visual perception, colors, and visual appearance of some key elements of the games. On closer inspection, the results show that the tendency to overload user interfaces with an abundance of interactive and visually enhanced features may reduce game enjoyment and overall satisfaction with the game, presumably due to factors such as information overload and cognitive distraction. In conclusion, it seems that the rule “less is more” could also be applied to the digital transition explained in this article.